In vitro Induction of Transmissive Resistance to Tetracycline, Chloramphenicol and Ampicillin in Vibrio cholera non-O1/ non-O139 Serogroups Isolated Within 1990-2005 - N. A. Selynskaya; I. V. Ryzhko; L. M. Verkina; A. V. Trishina; A. V. Mironova (Антибиотики и Химиотерапия, 2020)
Inducible character of resistance to tetracycline, chloramphenicol and ampicillin was investigated in 20 strains of Vibrio cholera non-O1/non-O139 serogroups isolated from inhabitants of Uzbekistan in 1990 (10 strains, ctx+) and in 2001 (5 strains, ctx-) and from inhabitants of Kalmykiya within 2003-2005 (5 strains, ctx-). Eight of the 20 isolates showed not only capacity for induction of the antibiotic resistance, but also its possible self transfer to Escherichia coli and reverse crosses in El Tor V.cholerae P-5879. It was shown that the effect of the antibacterial on the isolates phenotypic susceptibility could increase the resistance markers expression, when the genomes contained sites responsible for their expression, that required constant bacteriological control of the treatment efficacy and the use of the isolates antibioticograms for early replace of the inefficient drug by the efficient one. The prevalence of V.cholerae O1 and non-O1/non-O13 serogroups with multiple resistance to the antibacterial and the genetic potency for the antibiotic resistance development in the pathogen made difficult the choice of efficient drugs for prophylaxis and treatment of diseases caused by V.cholerae.